The Evolving Field of Graphic Design: Challenges and Opportunities in the Integration of Artificial Intelligence - Rosyida, Hanni Fadhilatul; Syafei, Ahmad; Nuha, Muhammad Ulin (International Journal of Graphic Design, 2025)
The integration of Artificial Intelligence (AI) has significantly transformed the landscape of graphic design, shifting the designer’s role from sole creator to visual curator and co-creator. While AI tools such as Midjourney and Adobe Firefly offer speed and efficiency in ideation and iteration, they also raise critical concerns regarding authorship, originality, and the redefinition of creative identity. This research seeks to investigate how professional Indonesian graphic designers view and adjust to the incorporation of AI in their creative processes. Using an interpretative phenomenological method, this study explores the lived experiences of ten designers from diverse professional backgrounds who actively integrate AI into their design practices. Data was gathered via semi-structured interviews and analyzed thematically using the Interpretative Phenomenological Analysis (IPA) approach. The results indicate five main aspects: changing job roles, conflicts between creativity and automation, adaptive learning approaches, ethical and professional challenges, and chances for improved design efficiency. Participants recognized that although AI enhances the creative process, it frequently tests their feeling of artistic control and prompts inquiries regarding the legitimacy of outcomes produced with AI assistance. Additionally, ethical issues like plagiarism and uncertainties around copyright surfaced as major concerns. This research adds to the discussion on digital design by emphasizing local perspectives in a worldwide technological transformation, illustrating how cultural and professional values influence the adaptation process. The findings provide important insights for educators, practitioners, and policymakers who seek to promote ethical, culturally aware, and critically reflective AI implementation in the creative sectors.